2014
DOI: 10.12980/apjtb.4.2014c1031
|View full text |Cite
|
Sign up to set email alerts
|

An initial study of insect succession on decomposing rabbit carrions in Harare, Zimbabwe

Abstract: Of the dipteran species collected during the study, L. cuprina and C. albiceps could be important for further forensic studies since they were collected from the carcasses and also observed from the rearing units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 15 publications
1
26
1
1
Order By: Relevance
“…Based on the results of previous research, Anderson (2011) reported that pig carcasses placed on outdoor decomposed faster than indoors. Observations of Mabika et al, (2014) carcasses of rabbit placed on outdoor without shade were faster than carcasses with shade. Similarly, Zeariya et al, (2015) carcasses of dogs and rabbits in Cairo.…”
Section: Decomposition Of Carcassesmentioning
confidence: 94%
“…Based on the results of previous research, Anderson (2011) reported that pig carcasses placed on outdoor decomposed faster than indoors. Observations of Mabika et al, (2014) carcasses of rabbit placed on outdoor without shade were faster than carcasses with shade. Similarly, Zeariya et al, (2015) carcasses of dogs and rabbits in Cairo.…”
Section: Decomposition Of Carcassesmentioning
confidence: 94%
“…The experiment was conducted on an animal suffering from cancer. This was a pioneering trial, since such research has hitherto involved only cancer-free cats, as well as other mammals, mainly pig or rabbit carcasses (35,36,44,54). Some of the studies concerned urban, rural, or forest environments and plantations (14,16,19,20,(23)(24)(25)(26).…”
Section: Tab 3 Period Of Development Of Calliphora Vicina At Selectmentioning
confidence: 99%
“…Species of blowflies are popularly known in Brazil as gadflies. Their larvae may be biontophagous or scavengers and can cause obligatory or optional myiasis, thus taking on great importance regarding animal health (Greenberg, 1971, Mabika et al, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…It has a significant role as a predatory other dipterous larvae. Moreover, this dipterous insect is of great importance with regard to public health because it mechanically carries pathogens to humans and animals (Queiroz et al, 1996;Mabika et al, 2012;Radhakrishnan et al, 2012;Marchiori, 2014aMarchiori, , 2014bMarchiori, , 2014c.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation